Taxonomic revision of the Odontophrynus cultripes species group, with description of a new related species (Anura, Cycloramphidae) - Caramaschi, Ulisses; Napoli, Marcelo Felgueiras (Zootaxa, 2012)
The revision of the O. cultripes species group is presented, through the definition and characterization of O. cultripes, theredescription of O. carvalhoi based on recently collected specimens, and the description of a new species. Odontophrynusmonachus sp. nov. is described from the headwaters of the São Francisco River, in the Parque Nacional da Serra da Ca-nastra (20o 10’S, 46o 30’W, 1350 m above sea level), Municipality of São Roque de Minas, State of Minas Gerais, Brazil. The geographic distributions of the referred species are described and mapped.